On the power, wisdom and goodness of God as manifested in the creation of animals and in their history, habits and instincts - Kirby, William, 1759-1850 (Bridgewater treatises on the power, wisdom, and goodness of God, as manifested in the creation, 1835)
"The prescribed object of the several treatises, of which the present forms one, is the illustration of the Power, Wisdom, and Goodness of the Deity, as manifested in the Works of Creation; but it is not only directed that these primary attributes should be proved by all reasonable arguments derived from physical objects, but also by discoveries ancient and modern, and the whole extent of literature. As the Holy Scriptures form the most interesting; portion, in every respect, of ancient literature; and it has always been the habit of the author of the present treatise to unite the study of the word of God with that of his works; he trusts he shall not be deemed to have stepped out of the record, where he has copiously drawn from the sacred fountains, provided the main tenor of his argument is in accordance with the brief put into his hands"--Introduction. (PsycINFO Database Record (c) 2008 APA, all rights reserved)